Engineering Tribology - Stachowiak, Gwidon; Batchelor, Andrew (Butterworth–Heinemann, 2013)
Engineering Tribology, 4th Edition is an established introductory reference focusing on the key concepts and engineering implications of tribology. Taking an interdisciplinary view, the book brings together the relevant knowledge from different fields needed to achieve effective analysis and control of friction and wear.Updated to cover recent advances in tribology, this new edition includes new sections on ionic and mesogenic lubricants, surface texturing, and multiscale characterization of 3D surfaces and coatings. Current trends in nanotribology are discussed, such as those relating to lubricants, coatings and composites, and geotribology is introduced.Suitable as an introductory text, a refresher or an on-the-job reference, Engineering Tribology, 4th Edition is intended for final year undergraduate and postgraduate students in mechanical engineering as well as professional engineers. It is also relevant to those working in materials engineering, applied chemistry, physics and bioengineering.